PENGARUH KEBERADAAN PABRIK CRUMB RUBBER PT. ANDALAS AGROLESTARI LOGAS TERHADAP PENDAPATAN PETANI KARET DI KABUPATEN KUANTAN SINGINGI PROPINSI RIAU - Ermi Tety; Syaiful Hadi; Sufre Vobe Andri (Fakultas Pertanian, Universitas Riau, 2011)
The aim of this research is to analyze and compare the returns of rubber tapper at farm levelwho sell rubber to rubber factory and that who sell rubber to whole seller. The researchresult show that farmers who sell rubber to factory have average return of Rp 5.571 millionper year per hectare with net profit of Rp 2.02 million. Farmers who sell outside the factoryhave average return of Rp 5.316 million with the net profit of Rp 1.085 million. The RCRfigure for farmers who sell rubber to factory is 1.57 while those who sell to outside factoryis 1.51. In general the rubber factory may have a positive impact to local farmers.Key words: rubber farmer, production cost, and revenue